Improving Teacher Performance through Effective Leadership, Work Discipline, and Work Motivation - Saputra, Rian Tri; Darmawan, Didit (Metromedia, 2023)
Education is the main foundation of a nation's development, and the quality of education is highly dependent on the performance of teachers. In Indonesian education, teacher performance is a key factor that determines the success of the learning process. This study aims to review the role of leadership, work discipline and work motivation on teacher performance in schools. The method used is a literature study by collecting relevant theories and research results on the influence of these factors on teacher performance. The results show that effective leadership, good work discipline and high motivation have a significant effect on improving teacher performance. Principals who are able to create a supportive climate, provide rewards and career development opportunities can motivate teachers to work better. Thus, the quality of education in schools can be achieved optimally.